The Dysregulation Profile Predicts Cannabis Use in the Offspring of Teenage Mothers. (11th November 2012) - De Genna, Natacha M.; Larkby, Cynthia; Cornelius, Marie D.
Abstract : Background . Offspring of teenage mothers are at greater risk of early drug use. Research has identified a child behavior checklist (CBCL) profile for children with high levels of comorbid behavior problems, the dysregulation profile (DP), as another risk factor for drug use. Method . Teenage girls (12–18 years old; 71% African-American, 29% White) were recruited during pregnancy. Data were collected during pregnancy and when offspring were 6, 10, and 14 years old (n = 318 ). Mothers completed the CBCL when children were at ages 6 and 10, and children who scored 60 or higher on all 3 DP subscales (aggression, anxiety/depression, and attention problems) were categorized as dysregulated. At ages 10 and 14, the offspring (50% male, 50% female) reported on their cannabis use and completed the childhood depression inventory (CDI). Results . DP at age 6 and depressive symptoms at age 14 predicted recent cannabis use in the offspring. There was a significant interaction between race and pubertal timing such that White offspring who matured earlier were at greater risk of recent cannabis use. Conclusions . The results of this study suggest that it may be possible to identify a subset of children at risk of dual diagnosis as early as age 6.